Microwave assisted synthesis method for cobalt nanoleaves and its usage in sensitive determination of lead in blue butterfly tea extract and tap water samples by flame atomic absorption spectrophotometry - Kartoglu, Bedrihan; Bahcivan, Aleyna; Erarpat, Sezin; Bayraktar, Ahsen; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2023)
Herein, cobalt nanoleaves (Co-NL) were synthesized by microwave assisted synthesis strategy and utilized as an adsorbent in cobalt nanoleaves based preconcentration method (CNL-PM) to preconcentrate lead at trace levels in blue butterfly tea extract and tap water. The adsorbent was characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) and Fourier transform infrared spectrometer (FTIR). Instrumental measurements were performed by slotted quartz tube-flame atomic absorption spectrometer (SQT-FAAS). Under the optimum conditions, limit of detection (LOD) and limit of quantification (LOQ) for the CNL-PM-SQT-FAAS system were 2.4 and 7.9 mu g/kg, respectively. Hence, FAAS enrichment factor was improved by 104.3-fold under optimum conditions. Recovery experiments for environmental application were conducted for two tap water samples to assess the method's applicability and accuracy. Further, developed method was applied to butterfly tea extract samples and lead concentration was found as 0.26 +/- 0.01 and 0.36 +/- 0.01 mu g/g for A and B tea samples, respectively.
Keywords: Cobalt nanoleaves; Lead; Blue butterfly tea; Tap water; Preconcentration method; Flame atomic absorption spectrophotometry; SOLID-PHASE EXTRACTION; MULTIWALLED CARBON NANOTUBES; LIQUID-LIQUID-EXTRACTION; ION-IMPRINTED POLYMER; EFFECTIVE ADSORBENT; ALPHA-COBALT; PRECONCENTRATION; NANOPARTICLES; CADMIUM; NICKEL; Chemistry; Food Science & Technology